Hypervariable region 1 shielding of hepatitis C virus is a main contributor to genotypic differences in neutralization sensitivity - Prentoe, Jannick (Hepatology, 2016)
There are 3-4 million new hepatitis C virus (HCV) infections yearly. The extensive inter-genotypic sequence diversity of envelope proteins E1 and E2 of HCV and shielding of important epitopes by hypervariable region 1 (HVR1) of E2 are believed to be major hindrances to developing universally protective HCV vaccines. Using cultured viruses expressing the E1/E2 complex of isolates H77 (genotype 1a), J6 (2a), or S52 (3a), with and without HVR1, we tested HVR1-mediated neutralization occlusion in vitro against a panel of 12 well-characterized human monoclonal antibodies (HMAbs) targeting diverse E1, E2, and E1/E2 epitopes. Surprisingly, HVR1-mediated protection was greatest for S52, followed by J6 and then H77. HCV pulldown experiments showed that this phenomenon was caused by epitope shielding. Moreover, by regression analysis of HMAb binding and neutralization titer of HCV we found a strong correlation for HVR1-deleted viruses, but not for parental viruses retaining HVR1. The inter-genotype neutralization sensitivity of the parental viruses to HMAbs AR2A, AR3A, AR4A, AR5A, HC84.26, and HC33.4 varied greatly (>24- to >130-fold differences in IC(50)-values). However, except for AR5A, these differences decreased to less than 6.0-fold when comparing the corresponding HVR1-deleted viruses. Importantly, this simplified pattern of neutralization sensitivity in the absence of HVR1 was also demonstrated in a panel of HVR1-deleted viruses of genotypes 1a, 2a, 2b, 3a, 5a, and 6a, although for all HMAbs, except AR4A, an outlier was observed. Finally, unique amino acid residues in HCV E2 could explain these outliers in the tested cases of AR5A and HC84.26. Conclusion: HVR1 adds complexity to HCV neutralization by shielding a diverse array of unexpectedly cross-genotype-conserved E1/E2 epitopes. Thus, an HVR1-deleted antigen could be a better HCV vaccine immunogen.